2021
DOI: 10.1016/j.jmb.2020.166795
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative SKP2 Interactions with CDK-Cyclin Complexes Support a Cyclin A-Specific Role in p27KIP1 Degradation

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Targeting SCF E3 ubiquitin ligases have been identified as a promising strategy for developing anticancer drugs. [37,38] Skp2, an F-box protein in the SCF complex, specifically recognizes p27, [39] and Skp2 expression is inversely correlated with p27 expression in many types of cancers. [37] Accumulative evidence has demonstrated that Skp2-targeted drugs can directly induce p27 accumulation and G1 phase cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting SCF E3 ubiquitin ligases have been identified as a promising strategy for developing anticancer drugs. [37,38] Skp2, an F-box protein in the SCF complex, specifically recognizes p27, [39] and Skp2 expression is inversely correlated with p27 expression in many types of cancers. [37] Accumulative evidence has demonstrated that Skp2-targeted drugs can directly induce p27 accumulation and G1 phase cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…95 Characterisation of the binding of SKP2 (S-phase kinase associated protein) to cyclin A has revealed how cyclin recruitment site promiscuity for binding SLiMs is increased by being able to recognise sequences in a ''reverse'' binding mode 96 and how mutations can both dial up and down affinity for competing proteins, in this example SKP2 vs. p27. 97 Cyclin B has provided the first example of a SLiM binding site on the C-terminal CBF (C-CBF) surface of a cell cycle cyclin. CDK1-cyclin B is the master mitotic regulator and phosphorylates many mitotic proteins to effect substantial cellular reorganisation to facilitate chromatid segregation and cytokinesis.…”
Section: Cdk-containing Macromolecular Complexesmentioning
confidence: 99%
“… 95 Characterisation of the binding of SKP2 (S-phase kinase associated protein) to cyclin A has revealed how cyclin recruitment site promiscuity for binding SLiMs is increased by being able to recognise sequences in a “reverse” binding mode 96 and how mutations can both dial up and down affinity for competing proteins, in this example SKP2 vs. p27. 97 …”
Section: Cdk-containing Macromolecular Complexesmentioning
confidence: 99%
“…S-phase kinase-associated protein 2 (Skp2) acts as an E3 ligase, and its Fbox domain can form SCF (skp1-cullin-F-box) complex with Skp1, Cullin1, and Rbx1 [ 7 ]. Skp2, as the E3 ligase of the SCF complex, regulates important cellular biological processes by recognizing substrates for ubiquitination and then degrades phosphorylated P27 Kip1 via protein-ubiquitin pathway or enhances interactions with other proteins and regulates protein activity, such as cell cycle, DNA repair, Akt activation, and mitosis [ 8 , 9 ]. For example, the SCF-Skp2 complex regulates the cell cycle by inhibiting degradation of p21 Cip1/Waf1 and p27 Kip1 by ubiquitin-mediated cyclin-dependent kinase (CDK) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%